The Intensifiers this/that in Some Varieties of English - Calle-Martín, Javier; Lorente-Sánchez, Juan (My University, 2020)
The intensifiers this/that acquired their adverbial status as a result of a grammaticalization process by means of which the deictic demonstratives became degree adverbs with the meaning of ‘to this/that extent, so much, so’ (OED s.v. this/that adv). The intensifier use of that has been traced back to the second half of the 14th century, originally associated with expressions of quantity like as much as that, as far as that, as long as that and eventually developing into proper degree words like that much, that far and that long, respectively. The use of this, on the other hand, developed in the second half of the 15th century. The phenomenon disseminated in the early 19th century as a typical resource of spoken English and since then, these intensifiers have found their room in the written domain imposing a scalar construal on adjectives for which scale is not the default construal. These intensifiers have been hitherto ignored in the literature, perhaps as a result of an erroneous accusation of informality, and consequently so has been traditionally recommended in these contexts. Despite the intensifiers this/that are observed in practically all the varieties of English worldwide, it has a variable distribution. The present study, therefore, contributes to the study of the development of these intensifiers in some varieties of English worldwide with the following objectives: a) to analyse their use and compare their distribution in different varieties of English; and b) to cast light on the lexico-semantic structure of the right-hand collocates. The evidence comes from the New Zealand, Indian, Singaporean and Philippines components of the Corpus of Global Web- based English. This corpus contains 1.9 billion words from 340,000 websites in 20 different English-speaking countries using a random selection of web pages and blogs, thus becoming the appropriate input for the study of the phenomenon in the varieties of English worldwide.
Keywords: Inglés (lengua); Gramática inglesa; Intensificadores; This/that; Variedades del inglés